Multiple Structural Breaks and Inflation Persistence: Evidence from China1. Issue 1 (March 2015) - Li, Tianfeng; Wei, June
Abstract : The degree of inflation persistence fluctuates more in developing countries than in industrialized countries. This is because there are more economic reforms in developing countries than in industrialized countries. Hence, it is important to study the inflation persistence in developing countries. The present paper investigates the pattern of inflation persistence in China, a developing and transitional economy. Specifically, the paper studies statistically the number of structural breaks in China's inflation persistence based on the monthly retail price index (MRPI) and the quarterly retail price index (QRPI) inflation series from 1983 to 2011. The findings show that there are five and three structural breaks in the MRPI and QRPI inflation persistence, respectively. The present paper also exposes a high degree of persistence over the whole sample period and a slight decline in the level of the persistence since 1994. Furthermore, the persistence of two inflation series does not change monotonously but with obvious cyclical patterns. Using these derived estimated structural breakpoints, likely causes of the breakpoints in inflation persistence are investigated. Finally, theoretical and practical implications are discussed.